An Experimental Investigation of the Progressive Failure of Sandstone and Its Energy Evolution Characteristics - Yan Chen; Baohua Guo (Advances in Civil Engineering)
In this research study, the progressive failure and energy evolution characteristics of sandstone samples with different sizes were explored under uniaxial and triaxial compression conditions. The characteristic stresses and strains were captured using the crack axial strain levels and dissipative energy. The results showed that, with the increase in the ratios of the height to diameter (H/D), the crack closure stresses increased, while the crack damage stresses decreased. However, the levels of both the crack closure stresses and crack damages were observed to increase with the H/D. With increase in the confining pressure, it was found that the crack closure and crack damage stresses increased, while their levels decreased. The strains of the crack closures, peak crack axial, and crack propagation were observed to decrease with the H/D, while the crack closure strain levels increased. Also, the crack propagation strains were observed to increase with the confining pressures, while the crack closure, peak crack axial, and crack closure strain levels decreased. The progress failure of the sandstone samples was also obtained based on the evolution characteristics of the dissipative energy. The relationship between the energy densities during each phase and the H/D was also analyzed. It was determined that, with the increasing of the H/D, the input, elastic, and dissipative energy densities displayed different evolution characteristics. Furthermore, with the increases in the characteristic stresses, the input and elastic energy densities were found to increase. The dissipative energy density displayed a slight increase with the increases in the peak strength, which resulted in variations with regard to the crack closures and crack damage stresses.